Numerische Validierung der experimentellen Daten eines optimierten HAWT - Numerical Validation of the Experimental Data of an Optimized HAWT - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Berger, Frederik; Seok, Julie; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
In this work, an optimized HAWT has been analyzed numerically for validating its experi-mental data. The 3-D steady state CFD simulations have been performed in Star CCM+ with the RANS k-ω SST turbulence model. A single blade is modelled in a 120± fraction of a cy-lindrical domain, using periodic boundaries. Rotational effects are modelled by a frozen rotor approach. The design and off-design performance are investigated. The power coefficient was in good agreement with experimental data. Of special interest are the limitations of steady CFD investigations for the case of partially stalled conditions. It is shown that RANS investigations can provide good power indication despite boundary layer separation and re-versal flow. Additional information that can be obtained from simulation such as radial flow, detached boundary layer and flow circulation are presented as well
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.numeri_37
Keywords: Numerical simulation; Optimization; HAWT